Making and Testing Sample Control on Determination of Nitrite Content in Water and Wastewater by Using UV-Visible Spectrophotometer - Erna Styani; Endang Sri Lestari; Ika Widiana; Muhammad Ramadhan (President University, 2019)
This study focused on Making and Testing sample control as reference material on determination of nitrite content in water and waste water by using UV-Visible Spectrophotometer. Sample control has been made to replaced Certified Reference Materials (CRM) for determination of Nitrite content in water and waste water by using UV -Visible Spectrophotometer. Substitute materials for CRM should be homogeneous and stable, so the homogenity and stability control sample that has been made in this study is tested by using standard referring to ISO Guide 35 , 2006. The result of this experiments shows that the values of Fstat and Ftable on homogenity test are 0.796 and 3.179 (Fstat < Ftable); while the values of tstat and table on the stability test are 0.431 and 2.101 (tstat < table), the mean of control sample concentration is 0,0435 mg / L. All test parameters have been qualified in accordance with ISO Guide 35 , 2006. The result of this research shows that the control of samples on the determination of Nitrite in water and waste water by using UV-Visible Spectrophotometer can be used as substitute for CRM and reference material.